Prenatal immobilization stress and postnatal maternal separation cause differential neuroendocrine responses to fasting stress in adult male rats. Issue 6 (30th December 2019) - Roque, Angélica; Ruiz‐González, Roberto; Pineda-López, Edel; Torner, Luz; Lajud, Naima
Abstract: Prenatal immobilization stress (PNS) and postnatal maternal separation (MS180) are two widely used rodent models of early‐life stress (ELS) that affect the hypothalamus–pituitary–adrenal (HPA) axis, cause behavioral alterations, and affect glucose tolerance in adults. We compared anxiety‐like behavior, coping strategies, and HPA axis activity in PNS and MS180 adult (4‐month‐old) male rats and assessed their glucose tolerance and HPA axis response after mild fasting stress. Both PNS and MS180 induced a passive coping strategy in the forced swimming test, without affecting anxiety‐like behavior in the elevated plus‐maze. Moreover, both PNS and MS180 increased the hypothalamic corticotropin‐releasing hormone expression; however, only MS180 increased the circulating corticosterone levels. Both early life stressors increased fasting glucose levels and this effect was significantly higher in PNS rats. MS180 rats showed impaired glucose tolerance 120 min after intravenous glucose administration, whereas PNS rats displayed an efficient homeostatic response. Moreover, MS180 rats showed higher circulating corticosteroid levels in response to fasting stress (overnight fasting, 12 hr), which were restored after glucose administration. In conclusion, early exposure to postnatal MS180, unlike PNS, increases the HPA axis response to moderate fasting stress, indicating a differential perception of fasting as a stressor in these two ELS models.